Sosialisasi Petanque Sebagai Olahraga Masa Kini - Ardo Okilanda; Arisman Arisman; Hikmah Lestari; Muhsana El Cintami Lanos; Mutiara Fajar; Siti Ayu Risma Putri; Sugarwanto Sugarwanto (Universitas Muhammadiyah Pringsewu, 2018)
The result of this sports socialization based Society Serving activity is increasing the knowledge and made the students understanding the benefits of Petanque. So, the students can produce a proud achievement against Senior High School 1 OKU, especially in sports. After the socialization, the students are expected more enthusiastic and willing to practice Petanque and can determine which sports are right to be followed in the future. All in all, the seeds of best athlete are rising since in Senior High School level.Keywords: Petanque, Socialization, Senior High School